Inflation linked bonds and monetary policy - Ceccacci, Silvia (2007)
This paper characterizes the demand of inflation indexed bonds under inflation targeting and price level targeting. The two main findings are the following. The demand of inflation linked bonds is higher under inflation targeting than under price level targeting. The demand of inflation linked bonds is time dependent under inflation targeting, while it is time-invariant under price level targeting.